Trends in Functional Programming. - Van Eekelen, Marko (Trends in Functional Programming., 2007)
Volume 6. This book presents latest research developments in the area of functional programming. The contributions in this volume cover a wide range of topics from theory, formal aspects of functional programming, transformational and generic programming to type checking and designing new classes of data types. Not all papers in this book belong to the category of research papers. Also, the categories of project description (at the start of a project) and project evaluation (at the end of a project) papers are represented. Particular trends in this volume are:. - software engineering technique.